Understanding dendritic cell immunotherapy in ovarian cancer. Issue 6 (2nd June 2016) - Drakes, Maureen L.; Stiff, Patrick J.
ABSTRACT: Introduction : Approximately eighty percent of patients with ovarian cancer are diagnosed with advanced disease. Even with cutting edge surgical techniques and the best regimens of standard therapies most patients relapse and die of drug resistant disease within five years of diagnosis. Dendritic cell (DC) immunotherapy can induce anti-tumor T cell immunity in patients and holds great potential in the era of modern anti-cancer treatment. Areas Covered : This review outlines critical factors regulating the outcome of DC immunotherapy in ovarian cancer, summarizes the important findings in ovarian cancer DC clinical trials, and discusses new directions which may improve the effectiveness of DC immunotherapy. Expert Commentary : Administration of DC vaccines with other forms of immunotherapy may enhance the efficacy of these treatments, ultimately increasing cures for this disease.